A scoping review and evaluation of instruments used to measure resilience among post-secondary students. (September 2022) - Linden, Brooke; Ecclestone, Amy; Stuart, Heather
Abstract: As mental health problems continue to increase among post-secondary populations, the need to develop effective initiatives designed to bolster students' resilience has increasingly been identified as a priority. Therefore, access to valid tools with which to measure the efficacy of these interventions is imperative. To date, a comprehensive assessment of existing instruments used to evaluate the construct of resilience among post-secondary student populations has not been conducted. The purpose of this study was to fill this gap by conducting a scoping review of literature detailing the use of resilience instruments and evaluating their quality based on suitability for use in the post-secondary setting and associated psychometric evidence. We identified a total of 78 records published between 2010 and 2022, extracting a total of 12 instruments. Using detailed criteria frameworks, each instrument was assessed in terms of suitability and quality of associated psychometric evidence for validity and reliability. The results of our study suggest that many of the instruments currently being used to assess resilience among post-secondary students may not be appropriate. The majority of the instruments included in our review were developed for use among general adult populations and not specifically designed for use in the post-secondary setting. Most instruments did not assess resilience in a comprehensive, holistic matter that addressed the ability to bounce back from adversity by drawing upon psychological, social, cultural, and environmental resources, as defined by recent research. Further, no instruments included in our review had published evidence in support of a complete psychometric analysis. The results of our evaluation suggest that the Connor-Davidson Resilience Scale (CD-RISC) is the most suitable instrument for measuring resilience among post-secondary populations due to its suitability, comprehensive assessment of the construct of resilience, and demonstrably strong psychometric properties for both the 25- and 10-item versions of the tool. Highlights: There is a need for access to valid and appropriate tools with which to measure post-secondary students' resilience. We identified a total of 12 instruments evaluating resilience among post-secondary student populations. The majority of the instruments were not designed for use in the post-secondary setting and were not comprehensive· We recommend the CD-RISC as the most suitable. We recommend the CD-RISC as the most suitable instrument for measuring resilience among post-secondary students.